2017
DOI: 10.1093/ajh/hpx111
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sacubitril/Valsartan (LCZ696) Compared With Olmesartan in Elderly Asian Patients (≥65 Years) With Systolic Hypertension

Abstract: Hypertension is a very common disease in the elderly (aged ≥65 years). 1 More than 50% of the elderly population has hypertension, 2 especially systolic hypertension, which arises primarily due to age-related changes in the arterial structure of large arteries, contributing to the large artery stiffness. 3 These changes lead to loss of arterial elasticity, 4 resulting in elevated systolic blood pressure (SBP) and widened pulse pressure (PP; difference between SBP and diastolic blood pressure [DBP]). 1 Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 35 publications
5
69
0
5
Order By: Relevance
“…ABPM studies showed that sacubitril/valsartan effectively reduced 24‐hour BP, including nocturnal BP, in both Western and Asian patients with hypertension . Data show that Asian patients with hypertension may respond particularly well to this agent …”
Section: Resultsmentioning
confidence: 99%
“…ABPM studies showed that sacubitril/valsartan effectively reduced 24‐hour BP, including nocturnal BP, in both Western and Asian patients with hypertension . Data show that Asian patients with hypertension may respond particularly well to this agent …”
Section: Resultsmentioning
confidence: 99%
“…Two studies [6,9] reported SBP and DBP in LCZ696 100 mg and ARBs. Compared with ARBs, LCZ696 100 mg caused a significant reduction in SBP (MD -1.58 mm Hg, 95% CI -2.09 to -1.07, p < 0.05) and DBP (MD -0.66 mm Hg, 95% CI -0.98 to -0.33, p < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [6,[9][10][11][12][13] reported SBP, DBP, 24 h ASBP, and 24 h ADBP in LCZ696 200 mg and ARBs. Compared with ARBs, LCZ696 200 mg caused a significant reduction in SBP (MD -4.94 mm Hg, 95% CI -6.54 to -3.35, p < 0.05), DBP (MD -2.24 mm Hg, 95% CI -2.74 to -1.75, 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sacubitril/valsartan could reduce dyspnea and blood pressure, and improved the left ventricular pathologic changes as assessed by echocardiography. Another study [103] reported the effect of sacubitril/valsartan versus olmesartan in 588 hypertensive Asian patients with a mean age of 70.7 years. Sacubitril/valsartan exhibited greater lowering of blood pressure compared to olmesartan, and no relevant side-effects were reported.…”
Section: Heart Failurementioning
confidence: 99%